Case Report: Spontaneous Rupture of Hepatic Hemangioma - Pan, Bing; Lyu, Shao-Cheng; He, Qiang (Frontiers in Medicine, 2022)
Background Hepatic hemangioma (HH) is a congenital vasal malformation that seemed like the most probable benign liver neoplasm, composed of masses of blood vessels, which are anomalous in arrangement and size. In most cases, HH is asymptomatic, and patients have an excellent prognosis. According to research, the location and size of the mass are correlated with the symptoms and complications. Reports of spontaneous rupture of HH have been less reported in the literature. In this emergency condition, dynamic contrast-enhanced CT scanning, especially triple-phase computed tomography (CT) with delayed imaging, is preferred. Case Presentation Here, we presented two middle-aged female patients with spontaneous rupture of HH in our hospital. Following an accurate diagnosis of enhanced CT and emergency surgery, patients recovered well and were discharged from the hospital. Conclusion Appropriate imaging studies, especially enhanced CT, and emergency surgery are indispensable for patients with spontaneous rupture of HH. As a surgeon, we need to pay attention to the asymptomatic patient with HH.